2014
DOI: 10.1039/c3ta14746k
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid porous polymers constructed from octavinylsilsesquioxane and benzene via Friedel–Crafts reaction: tunable porosity, gas sorption, and postfunctionalization

Abstract: Based on the multi-reaction sites of benzene in the Friedel–Crafts reaction with octavinylsilsesquioxane, hybrid polymers with tunable porosity were prepared.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
95
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 69 publications
(105 citation statements)
references
References 68 publications
10
95
0
Order By: Relevance
“…26 POSS has been incorporated into polystyrene via chemical graing, including ATRP, RAFT, anion polymerization, Friedel-Cras reaction etc., to form hybrid polystyrenes of various molecular architectures. 38 Consistent with this report, when TPS was used as a crosslinker, S BET was also monotonously enhanced with decreasing the ratio of TPS because of the increasing crosslinking density, which could lead to higher surface areas up to 989 m 2 g À1 . In addition, nonreactive octaphenethyl POSS was also used to prepare hybrid nanocomposites with PS via physical blending.…”
Section: Introductionsupporting
confidence: 82%
See 1 more Smart Citation
“…26 POSS has been incorporated into polystyrene via chemical graing, including ATRP, RAFT, anion polymerization, Friedel-Cras reaction etc., to form hybrid polystyrenes of various molecular architectures. 38 Consistent with this report, when TPS was used as a crosslinker, S BET was also monotonously enhanced with decreasing the ratio of TPS because of the increasing crosslinking density, which could lead to higher surface areas up to 989 m 2 g À1 . In addition, nonreactive octaphenethyl POSS was also used to prepare hybrid nanocomposites with PS via physical blending.…”
Section: Introductionsupporting
confidence: 82%
“…[23][24][25] As a silica-like cage compound, polyhedral oligomeric silsesquioxane (POSS) provides an excellent platform for synthesis of new inorganicorganic hybrid materials with enhanced thermal and mechanical properties. 38,39 It was observed that S BET increased with the increasing reactive sites of benzene, i.e. These hybrid polystyrene based on POSS exhibited the improved thermal stabilities, 27,28 viscoelastic properties, 29,30 magnetic properties 31 compared to the pristine polystyrene.…”
Section: Introductionmentioning
confidence: 97%
“…The adsorption capacity of CO 2 is also comparable to that of some metal-organic framework materials and SQ-based porous materials at the same measured pressure. [50,14,51] Therefore, porous cage polymer 1 is Figure 10. CO 2 adsorption isotherm of cage polymer 1 at 273 K and 101 kPa.…”
Section: Resultsmentioning
confidence: 97%
“…Gel materials offer SSA'so fu pt o1 300 m 2 g À1 some of the highest known systemsb ased on SQs. [15][16][17][18][19][20][21][22][23][24] Gel materials also offer solvent uptake up to 600 %b ymass. Vinyl groups can be incorporated into the systemso ffering post polymerization functionalization points and further crosslink density,e xtending the useful possibilities for these materials.…”
mentioning
confidence: 99%
“…Many highs urface area organic materialss uch as hyper-cross-linked styrene-divinylbenzene copolymers are made by the porogen methodw ith surface areas approaching 2000 m 2 g À1 .S ilsesquioxaneb ased materials fit into the second synthetic methodology,w hereby porosity introduction employs the monomer geometry coupled with controlled polymerization. [13][14][15][16][17][18][19][20][21] Most high surfacea rea materials containing silicon are made via sol-gelp rocessing of tri-and tetraalkoxysilanes. [22][23][24][25] Solgel processing employs acid-or base-catalyzed hydrolysis and condensation to form highly cross-linkedx ero-or aerogels depending on the drying method.…”
mentioning
confidence: 99%